METODE DRILL SEBAGAI UPAYA MENINGKATKAN PEMAHAMAN ILMU TAJWID SANTRI TPA BAITURRAHMAN COKROMENGGALAn - Utami, Latifah Kurnia; Mahmudin, Afif Syaiful (Abdi Panca Marga, 2023)
Baiturrahman TPA, which is located in Sambirejo hamlet, Cokromenggalan village, Ponorogo district, was established in 1955. TPA began to develop rapidly in 1988. In an educational institution, both formal and non-formal, of course there are several problems faced both in terms of learning strategies, facilities , educators and so on. Likewise, the Baiturrahman TPA also has a problem. The problem that is being faced is that students are not fluent in reading the Qur'an due to the lack of knowledge of students about makhorijul letters and tajwid knowledge. So that students in reading the Qur'an are in a hurry and do not pay attention to the length and the law of reading contained in the verse that is being read. Of these two problems, the researcher focuses more on the lack of knowledge of students about the science of recitation. The researcher gave an offer to the Baiturrahman TPA teacher. The offer is to use learning strategies in teaching tajwid. The strategy is to use a learning method. The method chosen by the researchers to use is the drill method. After the drill method runs in the TPA, students who take part in the TPA activities can follow it well. In addition, students can receive recitation material easily.